A Remarkable new Lepanthes (Orchidaceae: Pleurothallidinae) hidden in plain sight - Yeager, Justin; Iturralde, Gabriel A.; Ocupa Horna, Luis; Huayta Baltazar, Abel; Baquero R., Luis E. (Phytotaxa, 2022)
Here we describe a charismatic miniature orchid species, Lepanthes attenboroughii which for many years has been commonly found in private and public collections, misidentified as its related species, L. caprimulgus. The new proposed species, L. attenboroughii has inflated flowers with stripes similar to L. caprimulgus. Nevertheless, L. attenboroughii shows rounder flowers when compared to the longer, tubular flowers with a narrowing of the sepaline cup towards the middle of L. caprimulgus with flowers reminiscent of a peanut. Also, the hidden petals and lip are consistently different when the two species are compared in detail. Most remarkable in this new species are the inflated flowers with the free reflexed portion of the synsepal extending significally farther than the middle of the total length of the sepaline cup.